PENGARUH FRAUD HEXAGON TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Empiris Pada Seluruh Perusahaan Sektor Perbankan Yang Terdaftar Di BEI Periode 2017-2021) - Syahputra, Haiqal Fermi; Kamaliah, Kamaliah; Humairoh, Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
Financial statement fraud remains a significant issue in the banking sector,affecting stakeholders' trust and financial stability. This study investigates theimpact of the Fraud Hexagon model on financial statement fraud in Indonesianbanking companies listed on the Indonesia Stock Exchange (BEI) from 2017-2021. Using multiple linear regression analysis, the study examines the influenceof six fraud elements: pressure, rationalization, opportunity, capability, ego, andcollusion. The findings indicate that financial stability, auditor changes,ineffective supervision, CEO photo frequency, and government projectcollaborations significantly impact financial statement fraud. These resultshighlight the importance of strengthening corporate governance mechanisms andregulatory frameworks to prevent fraud. Keywords: Fraud Hexagon, Financial Statement Fraud, Banking Sector,Corporate Governance, Indonesia